Скрининг бактерий-антагонистов для экологически безопасной борьбы с фитопатогенами томатов - Великоселец, М. И.; Русских, И. А. (БНТУ, 2021)
The world potato and tomato is facing major economic losses due to disease pressure and environmental concerns regarding pesticides use. This work aims at addressing these two issues by isolating indigenous soil bacteria that can be integrated into pest management strategies. More than 80 strains of Bacillus-like and otherwise were isolated from several soils, also associated with vegetable agro-systems in Belarus. Screenings for antagonistic activities against P. infestans and F. oxisporum were performed, allowing the selection of 12 strains displaying growth inhibition of both pathogens under in vitro conditions. The antagonistic activities displayed by the selected strains indicated that versatile metabolites can be produced by the strains. Overall, this study showed that antagonistic indigenous soil bacteria can offer an alternative to the indiscriminate use of pesticide in local agro-systems.